Silicon-Mediated Modulation of Olive Leaf Phytochemistry: Genotype-Specific and Stress-Dependent Responses - Marin Cukrov; Velemir Ninkovic; Luna Maslov Bandić; Šime Marcelić; Igor Palčić; Mario Franić; Paula Žurga; Valerija Majetić Germek; Igor Lukić; Darija Lemić; Igor Pasković (Plants)
Secondary metabolites in olive (Olea europaea L.) leaves constitute a complex framework wherein phenylpropanoids, terpenoids, and secoiridoids in particular, serve as major contributors to olive plant resilience. Silicon (Si) stands as a mediator of defense mechanisms in plants, enhancing their protective responses and adaptability. A field trial on one-year-old plantlets of two metabolically distinct olive genotypes was conducted to investigate the effects of foliar-applied Si on the phytochemical profiles of locally treated leaves. Silicon’s systemic effects in juvenile leaves were also appraised. We accounted for intervarietal differences in nutrient uptake and conducted in situ measurements of physiological indices. The peak of the summer season and the onset of autumn were chosen as the two sampling time points. Intense summer conditions prompted metabolic adjustments that resulted in phytochemical profiles unique to each cultivar. These profiles were further significantly altered by Si while remaining genotype-specific, with substantial increases in prominent compounds like oleuropein (105% and 252%) and verbascoside (62% and 126%), depending on the genotype. As the pressure from environmental factors eased, the differences in Si-mediated phytochemical responses emerged. Silicon had a limited effect on the phytochemical profile of the resilient cultivar which acquired a metabolic steady-state, while it significantly altered the profile of its metabolically more versatile counterpart, resulting with a progressive increase in its oleuropein (37%) and verbascoside (26%) levels. These effects extended to untreated, juvenile leaves as well. While effective in altering and improving the phytochemical composition of olive leaves, Si acted in a manner that adhered to each genotype’s metabolic foundation. The intensity of environmental constraints, along with each cultivar’s inherent sensitivity to them, seems to be tied to silicon’s capacity to mediate significant phytochemical alterations. The extent of silicon’s prophylactic function may therefore be dependent on a genotype’s metabolic foundation and overall sensitivity, and as such it seems inseparable from stress and its intensity.